Time-decay Memristive Behavior and diffusive dynamics in one forget process operated by a 3D vertical Pt/Ta2O5−x/W device - Qi Wang (Nature Portfolio, 2017)
Abstract A time-decay resistive switching memory using a 3D vertical Pt/Ta2O5−x/W device architecture is demonstrated, in which horizontal W electrodes were fabricated, and vertical Pt electrodes was formed at the sidewall after oxide was deposited. Unlike conventional resistive switching, which usually form a conductive filament connect two electrodes, a weak conductive filament was formed from bottom electrode W to near top electrode Pt. The memory can be recovered with a time scale when the electrical stimulation is removed. However, different decay behaviors were observed in one decay curve, including rapid decay and slow decay processes. This can be a good simulation of different stages of forgetting. By a combination of the current decay fitting and the conductive analysis, the rapid decay and slow decay processes correspond to ion diffusion and electron detrapping, respectively.